El final del Antiguo Régimen en Italia (1780-1820) - Capra, Carlo (Cuadernos de Historia Moderna, 2009)
French Revolution’s effects were indubitable in all Europe, but especially in Italian Peninsula. The present essay follows the History of Italian States before, during and after the Napoleonic Wars. Last pages focus on an Italian historiography’s fundamental debate: the origins of Risorgimiento.